Modeling Accessibility to Emergency Obstetric Care in Mountain Region on Adonara Island, Eastern Indonesia - Kalista Ina Dai Nimun; Frederika Rambu Ngana; Ali Warsito; Jehunias Leonidas Tanesib (Journal of Applied Geospatial Information, 2022)
The geographical conditions of an area influence accessibility problems. The difficult geographical conditions caused travel time to the location of the obstetric emergency center to be very long. One of the causes of the high maternal mortality rate in Eastern Indonesia is the long time to travel to Basic Emergency Obstetrics Cares. This study aims to model the travel time to the PONED-Pelayanan Obstetri Neonatal Emergensi Dasar (Basic Emergency Obstetric and Neonatal Care-BEmONC) in a mountain region. The difficulties in access to obstetric care could cause maternal mortality in mountain regions. This study was done on the island of Adonara in the Flores Timur district. Adonara Island has a high maternal mortality rate. Modeling accessibility used a raster-based model to model travel time. The data used Landsat 8 imagery, Digital Elevation Model (DEM), and road network data to obtain a land cover layer. The Saga GIS travel time calculation tool is used to calculate the accumulated cost of travel time. The cost is based on the speed of travel through each land cover pixel to the location of the Puskesmas Waiwerang (PONED 1) and Puskesmas Waiwadan (PONED 2). The results of the travel time modeling show that people living in five sub-districts reach the two PONED locations in ≥ 1 hour. The longest time for people to travel to PONED is ≥ 6 hours from Ile Boleng sub-district because there is a mountain in the Ile Boleng sub-district. The scenario of adding one PONED shows that only people living in two sub-districts reach the PONED ≥ 1 hour. This spatial modeling of travel time to the location of the PONED (emergency obstetric care) can be used by local governments in eastern Indonesia to improve access to the location of basic obstetric emergency health centers in mountain areas.